Light bridges can suppress the formation of coronal loops. Issue 1 (10th July 2021) - Miao, Yuhu; Fu, Libo; Du, Xian; Yuan, Ding; Jiang, Chaowei; Su, Jiangtao; Zhao, Mingyu; Anfinogentov, Sergey
ABSTRACT: A light bridge is a magnetic intrusion into a sunspot, it interacts with the main magnetic field and excites a variety of dynamical processes. In the letter, we studied magnetic connectivity between a light bridge and coronal loops rooted at the sunspot. We used the data of the Atmospheric Imaging Assembly onboard the Solar Dynamics Observatory ( SDO ) to study the features of sunspots with light bridges. It is found that if a light bridge anchors at the umbra-penumbra boundary, the coronal loops could not be formed around the anchoring point. If the a light bridge become detached from the penumbra, the coronal loop starts to form again. The vector magnetogram provided by the Helioseismic Magnetic Imager onboard SDO shows that the anchoring region of a light bridge usually have an accompanying opposite minor-polarities. We conjugate that the magnetic field line could connect to these opposite polarities and form short-range magnetic loops, and therefore, coronal loops that extend to long-range could not be formed. A model of light bridge is proposed to explain the magnetic connectivity between a light bridge and the coronal loops. This model could explain many physical processes associated with light bridges.